2011
DOI: 10.1016/s0954-6111(11)70008-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function, oxidative stress and inflammatory markers in severe COPD exacerbation

Abstract: The oxidant/antioxidant imbalance was significantly pronounced in patients with COPD exacerbation for at least 24 hours following their admission and when they were clinically stable enough to be discharged. Increased oxidative stress, elevated systemic inflammation and decreased antioxidant defence were common in end-stage disease and particularly COPD patients with ischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 28 publications
(36 reference statements)
3
73
0
Order By: Relevance
“…Treatment of mice with the chemical chaperone 4-PBA improved MCC following CS exposure. Our data highlight the benefits of using chemical chaperones as therapeutics to preserve the function of critical proteins in response to noxious cellular stresses such as CS (79)(80)(81). The preservation of proteins required for cilia formation and/or ciliated cell integrity may reduce autophagic substrates and enhance MCC in smokers.…”
Section: Figure 10mentioning
confidence: 79%
“…Treatment of mice with the chemical chaperone 4-PBA improved MCC following CS exposure. Our data highlight the benefits of using chemical chaperones as therapeutics to preserve the function of critical proteins in response to noxious cellular stresses such as CS (79)(80)(81). The preservation of proteins required for cilia formation and/or ciliated cell integrity may reduce autophagic substrates and enhance MCC in smokers.…”
Section: Figure 10mentioning
confidence: 79%
“…In COPD, systemic (226) and local (219, 220) oxidative stress have been reported. Acute bouts of exercise (224,226) as well as acute exacerbation (329,337) increase the level of oxidative stress. Direct oxidative stress exposure (338) or indirect production of ROS through inflammatory response (339,340) induces proteolysis and increases expression of UbP components.…”
Section: Mechanisms Of Limb Muscle Dysfunction In Copdmentioning
confidence: 99%
“…It has been reported that enzyme activity is altered as a result of these polymorphisms. [2,5,6] In the present study, we aimed to investigate the association of COPD, in which oxidative stress is involved in pathogenesis, and PON1, which has antioxidant properties, with Q192R and L55M polymorphisms.…”
Section: Introductionmentioning
confidence: 99%